ANALYSIS OF THE RELATIONSHIP BETWEEN PLAGIARISM FACTORS AND THE MORAL VALUE OF AUTHORS - Fitriyani, Risma; Maulida, Siti; Novitami, Dini; Rakhman, Patra Aghtiar (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
Copyright infringement is a significant problem for academic and professional consistency, which is triggered not only by technological factors, but also closely related to the moral values of authors. This research focuses on analyzing the relationship between the factors that drive plagiarism and the moral dimension in the academic environment. By utilizing a critical discourse analysis approach based on Foucault's thinking, this research examines how plagiarism narratives are formed, how pressures stemming from systems and power relations affect the morality of writers, and identifies internal and external factors that trigger acts of plagiarism. A case study of plagiarism among Indonesian academics is outlined to illustrate the complexity of the interaction between external pressures, personal ethical weaknesses, and challenges faced by institutions. The findings of this study suggest that efforts to prevent plagiarism need to include strengthening the values of honesty, responsibility, and integrity, not only through technical methods, but also by building sustainable moral awareness.